Antimicrobial Susceptibility Testing of the Combination of Aztreonam and Avibactam in NDM-Producing Enterobacterales: A Comparative Evaluation Using the CLSI and EUCAST Methods - Linda Mei-Wah Chan; Doris Yui Ling Lok; River Chun Wai Wong; Alfred Lok-Hang Lee; Ingrid Yu-Ying Cheung; Christopher Koon-Chi Lai; Viola C. Y. Chow (Antibiotics)
Background: The combination of aztreonam (ATM) and avibactam (AVI) presents an important therapeutic option for carbapenem-resistant Enterobacterales, particularly the NDM-producing Enterobacterales. In 2024, both the CLSI and EUCAST published their methods in antimicrobial susceptibility testing for this combination of agents. Materials and Methods: Forty carbapenem-resistant Enterobacterales isolates, including Escherichia coli (n = 35), Enterobacter cloacae complex (n = 2), Klebsiella pneumoniae complex (n = 2), and Citrobacter freundii complex (n = 1) were included in this study. All isolates harbored the NDM carbapenemase except one, which had no known detected carbapenemases. Four antimicrobial susceptibility testing methods of the combination of ATM and AVI were evaluated on these isolates, including the CLSI broth disk elution (BDE) method, the disk diffusion (DD) method of aztreonam–avibactam (AZA) following the EUCAST breakpoints, the MIC test strip (MTS) method of AZA following the EUCAST breakpoints, and the gradient strip stacking (SS) method. BDE was used as the standard of comparison. Results: Using BDE as the standard of comparison, the AZA DD, AZA MTS, and SS methods had 100% categorical agreement (CA), 0% very major error (VME), and 0% major error (ME). The essential agreement (EA) between the AZA MTS and SS method was 57.5%. Conclusions: The AZA DD, AZA MTS, and the SS methods showed complete concordance with the BDE method. However, the MICs obtained from the AZA MTS and SS were not comparable.